Serum metallothioneins in childhood tumours-a potential prognostic marker - Kruseova, Jarmila; Hynek, David; Adam, Vojtech; Kizek, Rene; Prusa, Richard; Hrabeta, Jan; Eckschlager, Tomas (International journal of molecular sciences, 2013)
Metallothioneins (MT) are low molecular weight, cysteine-rich proteins maintaining metal ions homeostasis. They play a role in carcinogenesis and may also cause chemoresistance. The aim of the study was to explore the importance of MT serum levels in children suffering from malignant tumours. This prospective study involves examination of 865 samples from 172 patients with malignant tumours treated from 2008 to 2011 at University Hospital Motol. MT serum levels were determined using differential pulse voltammetry-Brdicka reaction. Mean MT level was 2.7 ± 0.5 μM. There was no statistically significant difference between MT levels in different tumours. We also did not find any correlation between MT levels and response to therapy or clinical stages. However, we found a positive correlation between MT levels and age (p = 0.009) and a negative correlation with absolute lymphocyte number (p = 0.001). The fact that patients who had early disease recurrence had lower MT levels during the treatment (complete remission 2.67 vs. recurring 2.34, p = 0.001) seems to be important for clinical practice. Accordingly we believe that there is benefit in further studies of serum MT levels in tumours.
Keywords: Infant; Humans; kojenec; dítě; Disease Progression; Biomarkers, Tumor; Child; Female; lidé; Metallothionein; nádorové biomarkery; předškolní dítě; ženské pohlaví; Male; Adolescent; prognóza; Neoplasms; nádory; progrese nemoci; metalothionein; mužské pohlaví; Child, Preschool; Prognosis; mladiství